Humorous Coping With Unrequited Love: Is Perspective Change Important? - Greve, Werner; Hauser, Johanna; Rühs, Farina (Frontiers in Psychology, 2021)
A large number of studies suggest that humor is associated with mental well-being and effective as a means of coping. However, it is less well-understood which mechanisms are effective for this particular function of humor. The present study examines whether processes of change of perspective, which are often regarded as constitutive for humor, could be an effective coping-factor when facing unrequited love as a specific psychological burden. In a questionnaire study, N = 148 persons aged 18–65 years (w = 96) with actual or past experiences of unrequited love reported on their subjective burden due to this experience, their self-esteem and satisfaction with life, two scales for humor (Multidimensional Sense of Humor Scale: MSHS, and a self-constructed scale: Humorous Change of Perspective, HCOP) and a coping scale which measure change of perspective in the confrontation with goal blockages (Flexible Goal Adjustment, FGA). Results indicated that the burden of unrequited love [operationalized objectively as actuality of experience (dichotomous) or subjectively as burden experienced] and both indicators of well-being were negatively associated. Multiple regression analyses showed that humor was a significant moderator of this relationship in nearly all combinations of operationalizations of humor and indicators of well-being: Higher levels of humor are associated with better well-being even when the perceived burden was high. In addition, the study examined whether the coping effect of humor can be partly or mainly attributed to the individual's capacity to perspective change as captured by FGA. When including this scale as a covariate in the regression models, the moderation effect for MSHS did not persist; however, for HCOP the moderation effect remained unchanged: the moderator effect of humorous change of perspective proved to be independent of FGA. Taken together the results suggest that perspective-changing skills play a significant role in the coping effect of humor in dealing with psychological burdens. However, depending on which humor facet is measured, the entailed perspective change may or may not appear to go beyond what the individual's FGA can account for. This suggests that the coping effect caused by humorous change of perspective includes aspects that are also discussed for other coping resources as well as its own, humor-specific aspects. Potential avenues for future studies are discussed both with respect to the necessity for replication and extension of the present study and to the determination of other potential alleviativing effects of other facets of humor.